2014
DOI: 10.4103/0019-509x.146793
|View full text |Cite
|
Sign up to set email alerts
|

Rural urban differences in breast cancer in India

Abstract: Context: Breast cancer incidence rates are high in developed countries and much lower in less developed countries including India. Aims: The aim of the following study is to compare breast cancer incidence rates in rural, urban and metro regions of India and to estimate risk of developing breast cancer associated with residence in a rural area. Settings and Design: Descriptive and analytical study design. Materials and Methods: We extracted age adjusted incidence rate from 26 population-based cancer registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 14 publications
4
28
1
Order By: Relevance
“…We expected that there would be differences between rural and urban areas because of perceived differences in lifestyle in terms of diet and environmental factors. Our results are in agreement with the study conducted in India in 2014 which showed that people living in urban area were better protected compared those in the rural area [25]. On the other side, a recent study in Uganda in 2016, has suggested no significant urban-urban difference in breast Ca risk [26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We expected that there would be differences between rural and urban areas because of perceived differences in lifestyle in terms of diet and environmental factors. Our results are in agreement with the study conducted in India in 2014 which showed that people living in urban area were better protected compared those in the rural area [25]. On the other side, a recent study in Uganda in 2016, has suggested no significant urban-urban difference in breast Ca risk [26].…”
Section: Discussionsupporting
confidence: 92%
“…The majority of these reported a protective effect of breastfeeding on breast Ca in pre-menopausal women [25, 50–52]. The protective effect of breastfeeding is thought to occur through differentiation of breast tissue and reduction in the number of lifetime ovulatory cycles [53].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing incidence of BC in the last decade has been particularly observed in countries with a medium or high Human Development Index [2]. Within India, there are substantial differences in BC incidence rates between rural and urban areas: rates observed in urban registries range from 29 to 35 per 100,000 women, whereas those observed in rural registries vary from 10 to 12 per 100,000 women [3]. Very few studies address the reasons for these rural-urban differences [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…(Table -2): It is observed from the study that 125 subjects amounting to 51.44% are hailing from rural areas while 48.56%(118) subjects belong to urban areas. usually it is evident that the incidence used to be less is rural areas due to adherence to the rural life style [9]. However, it is observed in the trends that the incidence is comparatively more in the rural areas and this observation may be attributed to the reasons such as low educational status, lack of awareness regarding the disease, lack of medical facilities for diagnosis and due to life style modifications.…”
Section: Methodsmentioning
confidence: 39%